Optimization of DNA isolation and PCR parameters in Myristica sp. and related gen- era for RAPD and ISSR analysis. - S Syamkumar, B Krishnamoorthy, TE Sheeja, K Johnson George, Jessy Jerome, R Sandeep Varma, S Syamku; Parthasarathy, V A (Journal of Spices and Aromatic Crops, 2008)
An efficient protocol for isolation of DNA from wild and related genera of Myristica rich inpolysaccharides and polyphenols was developed. The protocol utilizes CTAB (3%), 1.5% PVPand 0.3% ß-mercaptoethanol for isolation and RNase and phenol chloroform extraction forpurification. The yield of DNA ranged from 25-175 µg/g of fresh leaf tissue, with Knemaandamanica giving the highest yield. The present method yielded 10 times higher than theold methods. Characteristic patterns were generated on digestion of DNA by EcorI and HindIII restriction enzymes. PCR parameters were optimized using random primers (OPERONTechnology, USA). DNA concentration at 20 ng/reaction, annealing temperature of 45°C, 0.3mM dNTP in presence of 0.5 U of Taq DNA polymerase, and 2.0 mM MgCl2 and MJ ResearchGene Thermocycler was best. Successful amplification by ISSR and RAPD primers indicatedthat DNA is of good quality and free of polysaccharides and polyphenols.